Fondation d’une mémoire familiale dans la cité des Namnètes : le mausolée antique des Pellières à Saint-Herblain (Loire-Atlantique) - Frédéric Mercier (Gallia)
The preventive excavation conducted in 2006 on the site of Pellières, in Saint-Herblain (Loire-Atlantique), showed that the summit of the Loire’s north bank was repeatedly occupied from Prehistory to the present time. Remains from Antiquity are the best represented vestiges. This interfluve zone between the Loire and Chézine was subject, probably since the 1st c. AD, to a fragmented restructuration focusing on a new road axis linking the two ancient civitas capitals, Nantes/Condevicnum and Vannes/Darioritum. On the low part of the bank, in the locality of les Preux, the pars urbana of an ancient agricultural domain was identified in 1979. North of the lane, near the centre of the domain, a trapezoidal-shaped ditched enclosure was built on the slope. It surrounds a rectangular structure identified as a temple from its plan and characteristics (cella and pronaos). But some elements around the building point to a different analysis. In particular, the presence of cremated human bones in a pit illustrates the presence of a tomb or a funeral pyre. This was dated from the 1st or the beginning of the 2nd c. AD. Nearby, the remains of a Bronze Age funeral monument were found and fragments of Roman votive figurines were intentionally deposited between the upper blocks of this monument, thus showing that it was still used during Roman times for specific rituals. All this demonstrate that these structures were used as a private funerary area in relation with an ancient rural domain. This mausoleum was built on the summit of the plateau, in order to be seen from the lane and to incorporate the remains of a 2 000-year-old funerary monument in order to ensure the blessing and protection of the ancestors, while settling the family and clan into the domain. This mausoleum constitutes, for this reason, a foundation act of family memory.